PEMIKIRAN IBNU KHALDUN TENTANG PENDIDIKAN DAN RELEVANSINYA DENGAN PENDIDIKAN DUNIA - AL Manaf (LPPM STAI DARUSSALAM LAMPUNG, 2020)
This article aim to analyze Ibn Khaldun's thoughts on education and its relevance to modern world education. This research uses qualitative approach (Library Research) by analyzing the sources collected and summarized in the article. Result this research shows that education is not only a teaching and learning process that is limited by time and space, but education is a process where students are able to live, absorb and even capture natural events throughout the ages. Ibn Khaldun's thoughts are also very relevant to modern education when viewed from various aspects, namely educators, learning methods, curriculum and educational goals. Positive impact What is expected from the results of this study is the adoption of the concept of Modern Education with the Concept of Education according to Ibn Khaldun.